2016
DOI: 10.1002/ase.1653
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anatomy Boot Camp on Students in a Medical Gross Anatomy Course

Abstract: Lincoln Memorial University-DeBusk College of Osteopathic Medicine (LMU-DCOM) offers an optional three-week summer Anatomy Boot Camp course (ABC) to facilitate students' transition into medical school and promote retention of anatomy subject matter. The pre-matriculation program is a supplemental instruction course that utilizes a small group learning format. Boot camp instruction is led by teaching assistants and two anatomy professors. Enrollees gain early exposure to Medical Gross Anatomy (MGA) course subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Medical students will likely continue to vary in pre‐existing anatomy knowledge, particularly in Canada, where anatomy courses are not a prerequisite for admission to any medical school (AFMC, ). As such, optional dissection during medical school or educational interventions prior to medical school, such as anatomy “boot camps” (Herling et al, ) or pre‐courses (McNulty et al, ), may reduce differences in anatomy preparedness that exist in students early in medical training.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students will likely continue to vary in pre‐existing anatomy knowledge, particularly in Canada, where anatomy courses are not a prerequisite for admission to any medical school (AFMC, ). As such, optional dissection during medical school or educational interventions prior to medical school, such as anatomy “boot camps” (Herling et al, ) or pre‐courses (McNulty et al, ), may reduce differences in anatomy preparedness that exist in students early in medical training.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive differences in anatomical structures and physiological processes among the domestic species is well known, which adds a layer of additional stress and anxiety onto the 8 increased amount of material the students are expected to know. Exposure to anatomy prior to beginning a professional curriculum in the form of an anatomy precourse or boot camp has been shown to improve performance within that professional curriculum in both veterinary (8) and human medical (16) As outlined above, the field of anatomy education is presently lacking in methods to adequately predict student performance within a professional veterinary anatomy curriculum. A one-week anatomy precourse has been developed that is truncated in nature, relatively easy to offer to incoming students, yet still provides students with a framework of knowledge to build upon within the professional anatomy courses (8).…”
Section: Standardized Tests Including the Medical College Admission mentioning
confidence: 99%
“…A study by Hairrell et al () showed similar performance on the gross anatomy course in an osteopathic medical program between students who had participated in the summer four‐week pre‐course and those who had not. Another study in an osteopathic medical program demonstrated a difference in gross anatomy performance favoring students who participated in the summer pre‐matriculation program on both block examinations and the final course grade (Herling et al, ). A veterinary school study (McNulty et al, ) demonstrated that students with summer pre‐matriculation coursework not only scored better on the repeated material in veterinary gross anatomy, but the gains also carried over to improved performance over non‐participating students on subsequent gross anatomy examinations.…”
Section: Introductionmentioning
confidence: 99%